The Association between Socio-Demographic Profile and Lifestyle Practices with Nutritional Status: A Cross-Sectional Study among Seventh- Day Adventist Practitioners in Kuching, Sarawak - Myat Su, Bo; Cheah, Whye Lian; Khairur Aiman Redzuan, Hafiz Boon; Kimberley Erica, Frankie; Law Yueh, Hung; Tan, Hui Hui; Law, Leh Shii; Siti Maryam, Ahmad Kendong (UNIMAS Publisher, 2025)
The Seventh-Day Adventism recommends their followers to adopt a healthy diet, adequate physical activity, avoidance of addictive substances, fostering faith and hope to give meaning to life. This study aimed to investigate the association between socio-demographic profile and lifestyle practices with nutritional status in Seventh-Day Adventist (SDA) practitioners in East Malaysia. This was a cross-sectional study conducted among SDA members aged 18 and above between February and June 2023. The total of 323 respondents was drawn from five SDA Churches based on Kuching, Sarawak. Using questionnaires, data on socio-demographic characteristics, nutritional status, spiritual practice, lifestyle behaviours were collected. Anthropometry measurement was also taken in the survey. Data were analyzed using IBM SPSS version 29.0. The study found that SDA members have satisfactory religious beliefs and involvement. Minority were alcohol drinkers (24.1%) and current smokers (4%). About 35% of the respondents were involved in regular physical activities and mostly were obese (44%) with high abdominal obesity (67.5%). The univariate analysis showed that gender was significantly associated with nutritional status (BMI, p=0.022; waist circumference p<0.001; and waist-hip ratio p<0.001). The higher prevalence of BMI, waist circumference, and waist-hip ratio observed in women compared to men is associated with a combination of physiological, hormonal and lifestyle behaviours. These findings suggest the need for more effective interventions tailored to their daily routine.